Beyond technical barriers: enhancing onboard safety through human-machine interaction management in ammonia-powered ships - Abubakirov, Rustam; Yang, Ming (Journal of Progress in Safety & Security, 2025)
As the maritime industry advances towards decarbonization, ammonia is emerging as a promising alternative fuel. However, its use introduces significant safety risks to operating personnel arising from tasks inside ship compartments, such as engine or fuel preparation rooms. Given the acute toxicity of ammonia and the effects of space confinement, reducing the personnel risks to conventional levels through technical mitigation alone poses a considerable challenge. The reliance on mitigation of leak consequences, as emphasized in current regulations for ammonia, raises ethical concerns as well. The present work seeks to explore a broader perspective on onboard safety by examining both the direct and indirect factors influencing personnel risk during interactions with hazardous processes. By analyzing the role of human-machine interactions (HMI) in ship operations, the study offers insights into how HMI management can significantly reduce accident probabilities. Our discussion underscores HMI management as a pivotal strategy for mitigating ammonia-related risks, a contrast to the approaches used for conventional, non-toxic marine fuels. This paper proposes a framework for implementing an effective HMI management strategy, highlighting the benefits and complexities involved. One sentence summary: This study highlights the need for risk reduction in toxic spaces, explains why increasing ventilation and/or adding more detectors is not an effective solution, and proposes an alternative strategy.